Technological, physicochemical and sensory changes of upland rice in soaking step of the parboiling process - Fonseca, Flávia de Araújo; Soares Junior, Manoel S.; Bassinello, Priscila ZaczuK; Eifert, Eduardo da Costa; Garcia, Diva Mendonça; Caliari, Márcio (Acta Scientiarum. Technology, 2014)
The aim of this study was to evaluate the effect of combinations of soaking temperature and time during the parboiling on the technological, physicochemical and sensory quality of two upland rice cultivars. The milling degree for BRS Primavera and BRS Sertaneja cultivars ranged from 7.11 to 8.89 g 100 g-1 and 7.62 to 8.91 g 100 g-1and the head yield from 63.77 to 69.26 g 100 g-1 and from 73.22 to 75.40 g 100 g-1, respectively. The ash content for parboiled BRS Sertaneja increased up to 68%; regarding protein, the content increased up to 10% and for lipids, the values increased up to 86%, approximately, after processing. The higher the soaking temperature, the lower the milling degree and head yield. The parboiled rice BRS Primavera achieved higher contents of ash and lipid in relation to non-parboiled milled rice, while the BRS Sertaneja obtained higher ash, protein, lipid, and crude fiber contents. Parboiled rice samples had higher yield and cooking time than milled rice samples. The condition of soaking at 65°C for 60 min. and 60oC for 112 min. was sufficient for the acceptance of all sensory attributes evaluated in BRS Primavera, and 65oC for 420 min. in BRS Sertaneja.